Social support network to family caregiver of a patient with Spinal Muscular Atrophy I and II. - Rafael Barreto de Mesquita; Patrícia Moreira Costa Collares; Fátima Luna Pinheiro Landim; Cláudia Viot de Albuquerque Moura; Maria Teresa Moreno Valdés (Universidade de Fortaleza, 2010)
Objective: To assess the formal and informal support given to the family caregiver of a patient with Spinal Muscular Atrophy I and II. Method: This was a study with a qualitative approach developed in 2008 in the homes of informants and in the premises of the Hospital Infantil Albert Sabin in Fortaleza, Ceara, conducted with 13 mothers, primary caregivers for their ill children. For data collection we used both the interview and the instrument generator of the names and qualifier of the relations, adapted for this study. Quantitative data were processed using the programs UCINET NetDraw 6.123 and 2.38, while the qualitative data were organized based on the technique of the Collective Subject Discourse. The analyses were conducted by means of network maps and collective discourses raised by central ideas. Results: The formal social network of family caregivers was composed of 72 actors, among professionals in the areas of health, education and others, linked to 12 institutions. The informal network was comprised of 83 actors. It was found that the management of care, even when the caregiver has support from other people is a cause of stress and overload. Conclusion: It is evident the importance of applying Social Network Analysis as a tool for understanding structural features and the dynamics of social relations of family caregiver. Of a patient with spinal muscular atrophy. The analysis suggests the need for intervention in thestudy group as a way to contribute to the recognition and use of existing services, increasing the significance of the help provided by network interactions.